Analisis penyebab insomnia: Studi kasus pada salah satu warga Kampung Topeng - Hannani, Luthfia; Alfianto, Fahira (Maliki Interdisciplinary Journal, 2024)
Insomnia is a sleep disorder that is experienced by many people. Insomnia is a condition of poor sleep quality that is affected by difficulty falling asleep, frequent awakenings in the middle of the night, difficulty falling asleep again, and waking up too early so that sleep is disturbed and has a negative impact on a person's quality of life. In order to treat insomnia disorder optimally, it is necessary to identify the factors that cause it. Insomnia can be caused by many factors such as stress, anxiety, economy, work, etc. The purpose of this study is to find out in depth the causes of insomnia disorder in Kampung Topeng residents. Researchers used a qualitative approach with a case study method and data collection techniques through semi-structured interviews so that they can be carried out more flexibly than structured interviews. This research was conducted by interviewing one of the residents of Kampung Topeng who experienced insomnia disorder. The results revealed that the factors that cause insomnia disorder in the subject are economy, stress, and health. The subject's low economy causes stress and eventually results in insomnia disorder in the subject. To deal with the disorder, the subject needs to take medication and control the problem or cause of the stress he is experiencing. The subject also needs to maintain his health which affects his health. The low economy of Kampung Topeng residents makes it difficult for residents to get health services. Therefore, it is hoped that the government will provide health service assistance and education to the residents of Kampung Topeng about maintaining health.